THE DAY OF THE WEEK EFFECT TERHADAP RETURN SAHAM LQ45 (PERIODE FEBRUARI – JULI TAHUN 2015) - SITAMARDAWA, KUSUMASTUTI (Jurnal Ilmiah Mahasiswa FEB, 2016)
The day of the week effect is a daily stock behavior pattern in a week, where in the certain moment stock return will be higher or lower than another day, this is caused by differences of liquidity and investors psychological condition in addressing the market. This study tested the day of the week effect on ISEX using daily return data of LQ45 stock index period February until July 2015 using multiple linear regression test. Sample in this study is non-probability sampling with saturated sample of 45 company that registered in LQ45 index February-July 2015.Based on the result of multiple linear regression testing with dummy variable show that in Monday, Tuesday, Wednesday, Thursday, and Friday of trading day simultaneously has no significant effect on stock return, and partially in Thursday have the highest significant effect on stock return. Daily stock return pattern that appear from descriptive testing show that the highest return happen in Friday while the lowest return happen in Monday.Keywords : The day of the week effect, return, efficient market hypothesis, multiple linier regression, LQ45.